Visualization analysis of feminist translation research in China (2002–2021) based on CiteSpace - Sun, Fei; Wang, Xiaochen; Li, Hongbin; Wang, Siying (Frontiers in Education, 2023)
Based on 601 articles on feminist translation theory published in China National Knowledge Infrastructure (CNKI) in the last 20 years from 2002 to 2021, this article draws a scientific knowledge map and makes a visual analysis of the research articles on feminist translation theory in China using CiteSpace as a visual tool. It was found that (1) both the cooperation between researchers and between research institutions in the domain of feminist translation research in China was not strong; (2) the focus of feminist translation research in China is mainly on feminism, feminist translation theory, feminist translation, and translation; (3) according to the map of the time zone and keywords mutation, feminist translation research in China is constantly moving toward a decline after fast development.